2013
DOI: 10.4244/eijv8i12a212
|View full text |Cite
|
Sign up to set email alerts
|

Emerging indications, in-hospital and long-term outcome of balloon aortic valvuloplasty in the transcatheter aortic valve implantation era

Abstract: The number of BAV is increasing, mainly due to increased referral of high-risk patients and to the emerging indication of bridge for TAVI. In this complex population, BAV is relatively safe but two-year survival remains poor, and more effective and definitive treatments should be pursued in a timely fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
71
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 21 publications
10
71
1
5
Order By: Relevance
“…Our study confirms the observations of other authors [6,7], that currently BAV has favourable acute outcome with a low rate of major complications, and is an acceptable bridge to subsequent intervention in the very high-risk population not immediately suitable for definite therapy.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our study confirms the observations of other authors [6,7], that currently BAV has favourable acute outcome with a low rate of major complications, and is an acceptable bridge to subsequent intervention in the very high-risk population not immediately suitable for definite therapy.…”
Section: Discussionsupporting
confidence: 81%
“…A similar observation of worse prognosis of BAV in course of cardiogenic shock was established in the large analysis performed by Saia at al. [6]. They presented in-hospital mortality of 56.5% in patients who underwent BAV in the setting of cardiogenic shock compared with 2% in the stable subgroups of patients treated with BAV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Several studies have correlated the presence of renal insufficiency before the procedure with increased mortality. 9,17,18 A study of 262 patients at high surgical risk undergoing BAV showed that creatinine clearance ≤ 60 mL/min before the procedure is a strong predictor of mortality. 7 The absence of vascular complications in this study may be related to the use of sheaths with small calibre (10F) in all patients, as well as to the immediate withdrawal of the sheath.…”
Section: Discussionmentioning
confidence: 99%